Universal building mixtures on high-module silicate components - Bakhriev Nuritdin Fakhritdinovich; Odilova Gulbakhor Shairovna (International Journal on Orange Technologies, 2020)
The article presents data on the results of research on the development of universal building mixtures. An example of the use of a mixture for laying walls of silicate brick to provide solidity in conditions of high seismic activity is given. Methods for regulating the setting time of unburned alkaline binders on high-modulus silicate components are proposed.